APLIKASI KAMUS DIGITAL OBAT BERBASIS ANDROID - Tri Ferga Prasetyo; Imam Adi Kusumo (PROCEEDING STIMA)
Android is an operating system that is open source which provides the freedom for developers to develop an application. With the advantages of the android operating system, will help a lot of Android-based smartphone users to enjoy a variety of applications, one such application is the digital dictionary of this drug. The main purpose of a digital dictionary application of these drugs is to assist them in finding the types of drugs effectively and efficiently. The type of data used are secondary data where the data obtained from reference books and literature related to this thesis. There are several stages in the making of this application, the analysis, design, workmanship and evaluation of program models that have been produced . Digital dictionary application android-based medicine , can be used on Android-based smartphones with minimal version 2.2. Dalam testing these applications can run smoothly.Keywords: smartphone, dictionary application, android.